Cutaneous reactive angiomatosis associated with erythema ab igne. (25th November 2013) - Palmer, Matthew J; Lee, Adriene; O'Keefe, Rod
Abstract: We present the case of a 49‐year‐old man with an 18‐month history of an intermittently pruritic red‐brown reticulate eruption of the medial legs, with occasional blistering. There were areas of scale, crust and superficial erosions. The patient worked long overnight shifts standing in front of hot machinery wearing shorts, and spent time sitting in front of a heater at home. A clinical diagnosis of erythema ab igne (EAI) was made. This settled with heater avoidance and protection of the legs with long trousers, as well as a topical corticosteroid. Histology showed features of cutaneous reactive angiomatosis, a rare condition with various associations but only previously reported once in association with EAI.